Relationship between self-efficacy and self-care management of type 2 diabetes mellitus patients: A cross-sectional study - Martadinata, Umar Hasan; Soares, Domingos (Indonesian Journal of Health Services, 2024)
Background: Type 2 diabetes mellitus represents a major global health problem that requires continuous self-management to prevent complications and improve quality of life. Effective diabetes management depends not only on medical treatment but also on patients’ behavioral and psychological readiness, particularly self-efficacy in performing daily self-care activities. Objective: This study aimed to analyze the relationship between self-efficacy and self-care management among patients with type 2 diabetes mellitus. Methods: This study employed an analytical cross-sectional design conducted in the working area of Lubuk Batang Primary Health Center. The study population consisted of patients diagnosed with type 2 diabetes mellitus, and a total of 93 respondents were selected using the Slovin formula. Inclusion criteria included individuals aged ≥19 years, diagnosed with diabetes mellitus without acute complications, and willing to participate in the study. Data were collected using the Diabetes Management Self-Efficacy Scale (DMSES) and the Diabetes Self-Management Instrument (DSMI). Data analysis included univariate analysis to describe the characteristics of the variables and bivariate analysis using the Chi-square test to examine the relationship between self-efficacy and diabetes self-care management. Results: The results showed that most respondents demonstrated good self-efficacy (64.5%), while the majority of respondents had moderate levels of diabetes self-care management (60.2%). Bivariate analysis revealed a statistically significant relationship between self-efficacy and diabetes self-care management (p = 0.017). Patients with higher self-efficacy were more likely to demonstrate better diabetes self-care management compared with those with lower self-efficacy. Conclusion: Self-efficacy has a significant relationship with diabetes self-care management among patients with type 2 diabetes mellitus. Strengthening patient self-efficacy may improve diabetes self-management behaviors and support better disease control in primary healthcare settings.